Pengaruh Pemberian Curcumin Terhadap Perbaikan Fungsi Hepar Tikus Putih (Rattus Novergicus) yang diinduksi Parasetamol Dosis Tinggi - Yolanda Esperanza; Sulistiana Prabowo; Fitri Handajani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
Paracetamol has analgesic properties comparable to NSAIDs, but paracetamol have minimal side effects. Paracetamol is metabolized via sulfation and glucuronidation conjugation which is then excreted in the urine. A small part of the paracetamol has been changed to NAPQI. NAPQI will be detoxified by gluthathione. In high doses, there in an increase in NAPQI and a decrease in glutathione levels that results in oxidative stress and liver cell necrosis. Curcumin is often used as a traditional medicine to treat liver disease where it contains phenolic groups capable to scavenge free radicals. Curcumin extract can improve cellular responses to oxidative stress such as increasing the expression of Nrf2, SOD, and gluthathione. The purpose of this research was to know the effect of curcumin on the improvement of liver function in white rats (Rattus novergicus) induced by high dose  paracetamol. The design of this research was a descriptive research using literature studies from at least 15 international journals indexed by Scimago or national journals indexed by Sinta published in 2015-2020. Based on the journals used in this research, giving curcumin at a dose of 200 mg/kg BW/day for 2 weeks was effective in significantly increasing gluthathione levels in rats receiving high dose paracetamol. Giving curcumin at a dose of 100 mg/kg BW/day for 7 days can reduce AST and ALT activity in rats receiving high dose paracetamol, but the dose of curcumin that was more effective in reducing AST and ALT activity was 200 mg/kg BW/day for 2 weeks. This is because of curcumin which functions as a hepatoprotector that bind directly to the toxic metabolite of paracetamol, thereby reducing the use of glutathione and quench free radicals, so that oxidative stress in the liver decreased and gluthathione levels increased, AST and ALT activity decreased.